Loneliness amongst older people in Europe: a comparative study of welfare regimes - Nyqvist, Fredrica (Eur J Ageing, 2018)
Previous research implies that the extent of welfare state regime provision plays an important indirect role in the prevalence of loneliness in later life. The aim of this study was therefore to assess the association between quality of living conditions and level of social integration indicators and the absence of loneliness in five different welfare regimes. By incorporating welfare state regimes as a proxy for societal-level features, we expanded the micro-level model of loneliness suggesting that besides individual characteristics, welfare state characteristics are also important protective factors against loneliness. The data source was from the European Social Survey round 7, 2014, from which we analysed 11,389 individuals aged 60 and over from 20 countries. The association between quality of living conditions, level of social integration variables and the absence of loneliness was analysed using multivariate logistic regression treating the welfare regime variable as a fixed effect. Our study revealed that the absence of loneliness was strongly associated with individual characteristics of older adults, including self-rated health, household size, feeling of safety, marital status, frequency of being social, as well as number of confidants. Further, the Nordic as well as Anglo-Saxon and Continental welfare regimes performed better than the Southern and Eastern regimes when it comes to the absence of loneliness. Our findings showed that different individual resources were connected to the absence of loneliness in the welfare regimes in different ways. We conclude that older people in the Nordic regime, characterised as a more socially enabling regime, are less dependent on individual resources for loneliness compared to regimes where loneliness is to a greater extent conditioned by family and other social ties.